Introduction to computer modelling for the design of biodegradable medical devices - Pan, J.
This chapter defines the purpose and scope of this book as well as providing an overview on how computer modelling can help in the design of biodegradable devices. Three computer modelling techniques including molecular dynamics, Monte Carlo method and finite element method are outlined without mathematical details. Applications of these techniques to modelling biodegradation are introduced. These techniques form the general background for the current book. Finally, the chapter provides a brief introduction to the degradation pathway of biodegradable devices which leads to the degradation models that are presented in the following chapters. © 2015 Elsevier Ltd. All rights reserved.
Keywords: AUTOMOBILE BIODEGRADABLE DEVICES; COMPUTER MODELLING; DESIGN; FINITE ELEMENT METHOD; MOLECULAR DYNAMICS; MONTE CARLO METHOD